Unveiling the Potential of VELScope in Potentially Malignant Oral Lesion Early Detection for Future Dental Diagnosis Technology - Saputra, Daniel Adhie; Dea Permata; Amar Raikhan Qodri; Amandia Dewi Permana Shita (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Oral lesions range from innocuous to possibly dangerous, including oral cancer, which is the world's 16th most common malignancy. Early detection of oral cancer can enhance a patient's life expectancy by a decade, emphasizing the need of diagnostic instruments like VELScope. VELScope is a portable device that employs blue light to examine oral tissue, exposing natural fluorescence and emphasizing aberrant regions that would otherwise be invisible without the use of specialized equipment. Objectives: This review looks at the possibility of the VELScope for identifying oral lesions, since it has the potential to be a future dental diagnostic tool. Method: We began with 88 findings and reduced them down to 33 research regarding VELScope technology published in the previous five years. Following screening, we chose ten articles using the same criteria for all research. Results: VELScope uses fluorescence to identify both obvious and concealed oral lesions, which is especially useful when collagen loss occurs in normal tissues. While using autofluorescence requires knowledge, it assists in analyzing margins in probable pre- malignant oral conditions. VELScope, despite its limitations, has promise for early cancer diagnosis as technology develops. Conclusion: When utilized for early diagnosis, VELScope helps to reduce oral cancer mortality, reaching an 83% 5-year survival rate. While it has limits, continuous technical improvements have the potential to improve its accuracy, making it a vital tool for accurate early diagnosis and lowering oral cancer mortality.